2021
DOI: 10.1155/2021/6644827
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Multiomics Analysis of Genetics and Epigenetics Reveals Pathogenesis and Therapeutic Targets for Atrial Fibrillation

Abstract: Objective. This study is aimed at understanding the molecular mechanisms and exploring potential therapeutic targets for atrial fibrillation (AF) by multiomics analysis. Methods. Transcriptomics and methylation data of AF patients were retrieved from the Gene Expression Omnibus (GEO). Differentially expressed genes (DEGs) and differentially methylated sites between AF and normal samples were screened. Then, highly expressed and hypomethylated and lowly expressed and hypermethylated genes were identified for AF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…[22][23][24][25][26]28,29 Specifically, AF multiomic analysis on atrial tissues has provided novel into the molecular pathways implicated in the pathology. 4,32,50,51 However, the need of cardiac biopsies, has limited enthusiasm of this technology to a small subpopulation of AF including those with valvular heart disease or CHD, for whom surgical intervention is already warranted. To overcome this, a surrogate tissue source is warranted to provide an indirect epigenetic and/or transcriptional phenotyping to mirror the failing myocardium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[22][23][24][25][26]28,29 Specifically, AF multiomic analysis on atrial tissues has provided novel into the molecular pathways implicated in the pathology. 4,32,50,51 However, the need of cardiac biopsies, has limited enthusiasm of this technology to a small subpopulation of AF including those with valvular heart disease or CHD, for whom surgical intervention is already warranted. To overcome this, a surrogate tissue source is warranted to provide an indirect epigenetic and/or transcriptional phenotyping to mirror the failing myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Genome-wide association studies and network analyses have identified specific loci and genes associated to AF concerning ion channels, transcription factors, fibrosis, extracellular matrix remodelling and contractile/structural proteins. [2][3][4][5][6] Furthermore, a large proportion of AF-associated genetic variants resides within noncoding regions, thus inferring that the genetic risk of AF occurs via regulatory mechanisms that culminate in atrial electrical and structural remodelling. 7,8 A mounting body of scientific evidence also supports the link between innate and adaptive immune responses and AF [9][10][11][12][13][14] ; nevertheless, the exact mechanisms whereby immunologic changes confer disease pathogenesis is still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a mouse study, the expression of chemokines or cytokines in CCR2 + macrophages increased after myocardial injury, indicating that monocytes are recruited to the injured sit [38] . A recent study found that CCR2 is a key gene associated with AF progression [39] . The high number of CCR2-positive monocytes/macrophages in the LAA of patients with progressive atrial remodeling in AF may suggest enhanced monocyte/macrophage in ltration.…”
Section: Discussionmentioning
confidence: 99%